HUBUNGAN ANTARA KEGIATAN PENYULUHAN PERTANIAN DENGAN PROGRAM PEMBERDAYAAN MASYARAKAT DI KECAMATAN BANYUDONO KABUPATEN BOYOLALI - Wijianto, Arip; Widiyanti, Emi (Universitas Sebelas Maret, 2008)
Extension activiry ar district Banyudono regency Boyolali cover need development to do changes, move society to do change and stabilize connection with target society. Society enableness program at Banyudono cover farmer institute capacity reinforcement, society participation enhanced in course of development, and enhanced self supporting and farmer independence. Found connection significant between extension activity with village society enableness program at Banyudono regency Boyolali